The effect of dietary nutrients on osteochondrosis lesions and cartilage properties in pigs - N Z Frantz; G A Andrews; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2006)
A total of 80 gilts (PIC 327 × 1050; 86 lb initial BW) were used in an 84-d study to determine the effect of different nutrients on the occurrence of osteochondrosis (OC) lesions, several cartilage criteria, growth performance, and carcass composition. Eight dietary treatments were formulated, consisting of 1) control (standard corn-soy diet, 3.5% choice white grease (CWG)) or the control diet plus 2) fish oil (3.5%) replaced CWG, 3) proline and glycine (Pro/Gly; 300 and 200% of lysine), 4) leucine, isoleucine, and valine (BCAA; 200, 100, and 100% of lysine, respectively), 5) silicon (1,000 ppm), 6) copper and manganese (Cu/Mn; 250 ppm and 100 ppm, respectively), 7) methionine and threonine (Met/Thr; 150 and 100% of lysine), and 8) combination of ingredients in diets 2 through 7. The diets were formulated slightly in excess of the pig's requirement for lysine and to meet minimum true ileal digestibility (TID) ratios for the other essential amino acids. The diets were also formulated to be isocaloric by slightly adjusting the fat (CWG) content, and were fed in three phases (1.07, 0.94, and 0.80% TID Lys). Upon completion of the feeding period, pigs were harvested, and the distal aspect of the left femur was evaluated by gross examination for OC lesions. The external surface was evaluated for abnormalities and given a severity score. Then each femur was sliced into 3-mm sections, and lesions were assigned a severity score for the underlying articular cartilage, and physeal growth plate. Overall (d 0 to 84), growth performance was unaffected by dietary treatment (P>0.21). Pigs fed diets containing fish oil or silicon tended (P<0.07) to have a higher severity score for external abnormalities (or defects in cartilage surface), compared with pigs fed the other dietary treatments, with pigs fed the control diet, Pro/Gly, or Cu/Mn intermediate. Pigs fed high Met/Thr, Cu/Mn, or silicon tended (P<0.08) to have lower articular cartilage severity scores than scores of pigs fed the control diet or BCAA, with the other dietary treatments intermediate. The occurrence of OC lesions at the growth plate, total faces with lesions, and total number of abnormalities were not affected by dietary treatment (P>0.23); there was a trend (P<0.14) for pigs fed diets containing high Met/Thr or fed the combination diet to have lower total severity scores than scores of pigs fed the control diet or fish oil, with the other treatments intermediate. Pigs fed additional Cu/Mn, Met/Thr, or the diet containing all additional ingredients had lower overall severity scores (P<0.03) than did pigs fed the control diet or fish oil. Cartilage compression or shear force were unaffected by dietary treatment (P>0.19), but pigs fed fish oil had a higher ratio for compression: shear energy (P<0.03), compared with the ratio for those fed the control diet, Cu/Mn, or silicon; the other treatments were intermediate. In summary, feeding pigs a diet containing additional silicon, Cu/Mn, Met/Thr, or a combination of these ingredients may offer the potential to reduce the incidence of osteochondrosis in gilts; more research will be required to verify these results.; Swine Day, 2006, Kansas State University, Manhattan, KS, 2006
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-83-S; Swine day; 2006; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 966; Cartilage; Finishing pigs; Swine; Osteochondrosis